Invisible farmers in Pakistan : a study on the role of women in agriculture and the impact of pesticides on them - 425886 Nasira Habib; Mourin, Jennifer; KHOJ (Research and Publication Centre) (Lahore, Pakistan : Pesticide Action Network Asia and the Pacific (PAN) Asia and the Pacific, 1986)
99